تحديث الخطاب الأدبي: قراءة في الأنماط الثقافية العربية المعاصرة (Journal of the College of Basic Education, 2026)
Modernizing the Literary Discourse: A Study in Contemporary Arab Cultural Patterns.The modernization of Arab literary discourse seeks to deconstruct traditional binaries between heritage and modernity through the interaction of texts with shifting cultural realities. Novels and poetry are redefining identity through concepts liberated from monolithic historical narratives, while modernization efforts manifest in adopting hybrid narrative styles that draw from myth and digital technology. Literary innovation extends beyond form to activate dialogue with cultural "margins," such as youth and women’s voices, through texts that reject ideological rigidity and redefine symbolic power structures. This transformation represents an attempt to restore Arabic literature’s role as a vital space for generating critical awareness of contemporary challenges, while remaining interconnected with global cultural and creative entanglements.